Meningitic Escherichia coli K1 Penetration and Neutrophil Transmigration Across the Blood–Brain Barrier are Modulated by Alpha7 Nicotinic Receptor - Chi, Feng (Public Library of Science, 2011)
Alpha7 nicotinic acetylcholine receptor (nAChR), an essential regulator of inflammation, is abundantly expressed in hippocampal neurons, which are vulnerable to bacterial meningitis. However, it is unknown whether α7 nAChR contributes to the regulation of these events. In this report, an aggravating role of α7 nAChR in host defense against meningitic E. coli infection was demonstrated by using α7-deficient (α7(-/-)) mouse brain microvascular endothelial cells (BMEC) and animal model systems. As shown in our in vitro and in vivo studies, E. coli K1 invasion and polymorphonuclear neutrophil (PMN) transmigration across the blood-brain barrier (BBB) were significantly reduced in α7(-/-) BMEC and α7(-/-) mice. Stimulation by nicotine was abolished in the α7(-/-) cells and animals. The same blocking effect was achieved by methyllycaconitine (α7 antagonist). The tight junction molecules occludin and ZO-1 were significantly reduced in the brain cortex of wildtype mice infected with E. coli and treated with nicotine, compared to α7(-/-) cells and animals. Decreased neuronal injury in the hippocampal dentate gyrus was observed in α7(-/-) mice with meningitis. Proinflammatory cytokines (IL-1β, IL-6, TNFα, MCP-1, MIP-1alpha, and RANTES) and adhesion molecules (CD44 and ICAM-1) were significantly reduced in the cerebrospinal fluids of the α7(-/-) mice with E. coli meningitis. Furthermore, α7 nAChR is the major calcium channel for nicotine- and E. coli K1-increased intracellular calcium concentrations of mouse BMEC. Taken together, our data suggest that α7 nAChR plays a detrimental role in the host defense against meningitic infection by modulation of pathogen invasion, PMN recruitment, calcium signaling and neuronal inflammation.